Dumpster Diving in the Gut: Bacterial Microcompartments as Part of a Host-Associated Lifestyle - Jakobson, Christopher M.; Tullman-Ercek, Danielle (PLoS pathogens, 2016)
Bacterial microcompartment function and the coordinated invasion of the host gut by Salmonella enterica. (a): A substrate molecule enters the microcompartment and is converted to an aldehyde species, which is trapped in the microcompartment shell before being converted either to an alcohol or to a Coenzyme A-conjugated species [32]. (b) The invading pathogen population enters the gut. (c) Each pathogen cell undergoes a fate decision between type III secretion (~10%-35% of cells) and microcompartment formation (~65%-90% of cells). (d) Type III secretion-competent cells invade the host epithelium while microcompartment-competent cells form microcompartments and synthesize vitamin B12. (e) Type III secretion-competent cells traverse the epithelium and undergo phagocytosis in the lamina propria. (f) Gut inflammation causes thiosulfate oxidation to tetrathionate, allowing microcompartment-mediated metabolism and pathogen proliferation. http://dx.doi.org/10.1371/journal.ppat.1005558.g001 What Are Bacterial Microcompartments and What Are They For? All of these metabolic pathways proceed through toxic aldehyde intermediates, and it is proposed that the microcompartment shell functions to protect the rest of the bacterial cell contents from these toxic compounds as well as to sequester a private pool of the requisite cofactor molecules [8].